2017
DOI: 10.1136/archdischild-2017-313574
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of retinopathy of prematurity (ROP) and ROP treatment in Switzerland 2006–2015: a population-based analysis

Abstract: The incidence of ROP treatment in Switzerland is low and was stable over the analysed period. The low incidence of sROP in patients with a GA of 29 weeks or more leaves room for a redefinition of ROP screening criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 23 publications
4
41
3
5
Order By: Relevance
“…Gerull et al (13) recently confirmed the low incidence of ROP in Switzerland in more mature infants than those included in our second study -those between 30 + 0 and 31 + 6 weeks of gestation. There was a very low incidence of any ROP (1.7% (56/3222)) and severe or treated ROP (0.16% (5/3222)) and these authors called for a review of screening criteria.…”
Section: Key Notessupporting
confidence: 77%
“…Gerull et al (13) recently confirmed the low incidence of ROP in Switzerland in more mature infants than those included in our second study -those between 30 + 0 and 31 + 6 weeks of gestation. There was a very low incidence of any ROP (1.7% (56/3222)) and severe or treated ROP (0.16% (5/3222)) and these authors called for a review of screening criteria.…”
Section: Key Notessupporting
confidence: 77%
“…This is an issue in particular in Switzerland with its very low prevalence of ROP treatment of 4.3% compared to other countries like Canada (10.4%), United Kingdom (8.5%), or Australia and New Zealand (7.3%) in preterm infants below 28 weeks. 4,11 The aim of this study was to assess if the screening criteria for ROP can be optimized in very low birth weight (VLBW, birth weight below 1500 g) infants in Switzerland. All VLBW infants live-born between 2006 and 2015 in Switzerland were included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from Gerull et al also showed decreasing mortality of preterm infants in Switzerland, but with stable incidence of ROP, during an earlier study period from 2006 to 2015. It was also documented that the incidence of ROP in Switzerland was lower than in other countries . In Europe, several recent studies have described an increasing incidence of treatment‐requiring ROP in recent years .…”
Section: Discussionmentioning
confidence: 73%
“…Relative to other countries, Switzerland had a very low incidence of ROP and ROP requiring treatment of 9.3% and 1.2%, respectively. The low incidence of ROP in Switzerland was documented as being stable in the period from 2006 to 2015 . Despite this low incidence, we had observed an apparent increase in the incidence of the severest ROP stage and ROP requiring intervention during ROP screening at our institution after 2015.…”
Section: Introductionmentioning
confidence: 74%